2017
DOI: 10.1007/s00345-017-2075-8
|View full text |Cite
|
Sign up to set email alerts
|

The “old” 15 mm renal stone size limit for RIRS remains a clinically significant threshold size

Abstract: While the overall SFR following RIRS for renal stones up to 2 cm is generally high, the SFR for 15-20 mm stones is significantly lower, with a longer operating time and hospital stay, and a higher complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…8 In RIRS, this tool is used to provide access to the ureter, to define the renal collection system, to reach the stone, and to insert stents and guidewires. 9,10 In diagnosis and treatment of urinary stones, the use of fluoroscopy has become widespread, and thus patients and surgical team were exposed to higher amounts of radiation. 11 The amount of exposed radiation depends on many factors such as the procedure performed, equipment at hand, and the technique used.…”
Section: Discussionmentioning
confidence: 99%
“…8 In RIRS, this tool is used to provide access to the ureter, to define the renal collection system, to reach the stone, and to insert stents and guidewires. 9,10 In diagnosis and treatment of urinary stones, the use of fluoroscopy has become widespread, and thus patients and surgical team were exposed to higher amounts of radiation. 11 The amount of exposed radiation depends on many factors such as the procedure performed, equipment at hand, and the technique used.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these studies have stated that as the stone size increased, the success of the surgery decreased. Also, they found that rising stone size could increase the possibility of residual stones [21-23]. Contrary to other studies, Ho et al [24] found that stone size did not affect SFR in their study.…”
Section: Discussionmentioning
confidence: 76%
“…In studies evaluating the efficiency of RIRS in lower pole stones, it was shown that the presence of lower calyx stones significantly reduces SFR [25, 26]. On the other hand, contrary to these data, a study showed that there was no relation between stone localization and SFR [21]. Similarly, Martin et al [27] and Ho et al [24], in their study, stated that RIRS had a similar efficiency in lower pole stones and other stones.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Stone size and/or volume have/has been reported to significantly affect SFR in RIRS. [12,13] Goldberg et al [12] reported a significantly lower SFR (85%) in renal stones >15 mm. The mean preoperative time, hospital stay and complication rate were also higher in patients with renal stones larger than 15 mm.…”
Section: Discussionmentioning
confidence: 97%